Interdialytic Weight Gain and Nutritional Status are Associated with Quality of Life Among Hemodialysis Patients in Dr. Mohammad Hoesin General Hospital Palembang - Indah Listari Salsabila; Yuliarti Yuliarti; Fatmalina Febry; Ditia Fitri Arinda (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Hemodialysis patients experience changes in all aspects of their life, particularly due to fluid and dietary restrictions. Excessive interdialytic weight gain and malnutrition are common problems that negatively impact the increase of morbidity and mortality in these patients, as well as a decrease in their quality of life. This research aims to determine the relationship between interdialytic weight gain and nutritional status with the quality of life of chronic kidney disease patients undergoing hemodialysis at Dr. Mohammad Hoesin General Hospital Palembang. 102 patients were involved in this cross-sectional study, and they were taken by purposive sampling. IDWG data was collected using The Interdialytic Weight Gain (IDWG) observation sheet, nutritional status was identified using the Dialysis Malnutrition Score (DMS), and quality of life was assessed using The Kidney Disease Quality of Life Short Form-36 (KDQOL-36TM). The data analysis used in this study is Fisher Exact test. Based on The Fisher Exact test, there is a relationship between IDWG and quality of life (p=0.048). The results of statistical analysis also showed a relationship between nutritional status and quality of life (p=0.047). Most patients had IDWG in the mild category, good nutritional status, and poor quality of life based on KDQOL-36TM. This study concludes a relationship between interdialytic weight gain and nutritional status with the quality of life of patients undergoing hemodialysis. It is recommended that health workers in hemodialysis units monitor interdialysis weight gain regularly and conduct routine nutritional screenings to prevent a decrease in quality of life.